Efficacy and safety of plasma exchange in interstitial lung diseases with anti-melanoma differentiation-associated 5 gene antibody positive clinically amyopathic dermatomyositis. (2nd January 2023) - Komai, T; Iwasaki, Y; Tsuchida, Y; Hanata, N; Tsuchiya, H; Harada, Hiroaki; Hamasaki, Y; Nangaku, M; Shoda, H; Fujio, K
Abstract : Objective: Clinically amyopathic dermatomyositis (CADM) patients frequently develop refractory interstitial lung disease (ILD), with a poor prognosis. We aimed to verify the efficacy and safety of plasma exchange (PE) treatment for ILD in CADM. Method: A retrospective case–control study was conducted to compare clinical outcomes with and without PE treatment in CADM-ILD patients refractory to combination therapy of high-dose glucocorticoids, calcineurin inhibitors, and cyclophosphamide. Among 19 enrolled patients, 11 were further treated with PE. We compared survival rates and other clinical characteristics. PE consisted of either fresh-frozen plasma or albumin as a replacement solution. Results: Basal clinical characteristics at diagnosis, including age, gender, serum ferritin, Krebs von den Lungen-6 (KL-6), C-reactive protein, and respiratory function tests, did not differ between the two groups. The survival rate for treatment with PE was higher than for treatment without PE (91% and 50%, respectively, p < 0.05). Among PE-treated patients, anti-melanoma differentiation-associated gene-5 (anti-MDA-5) antibody titre, ferritin, and KL-6 as serological activity markers were sustainably reduced only after initiating PE. Therapeutic intervention with PE reduced the frequency of exacerbation of ILD requiring methylprednisolone pulse therapy. The occurrence of bacterial, fungal, and cytomegalovirus infection did not differ between the groups with and without PE, and adverse events associated with PE resolved with appropriate intervention. Conclusion: Combination therapy with PE was associated with an improved survival rate, and may be effective for the management of refractory ILD in CADM patients. A personalized therapeutic strategy including PE could be introduced for fatal rapidly progressive ILD.